THE ROLE OF PHYSICAL EDUCATION AND SPORTS IN THE EDUCATION OF A DEVELOPED GENERATION (Proceedings of International Educators Conference, 2022)
The article talks about a healthy lifestyle, physical exercises, physical training activities and their importance in raising a mature generation.